Regulatory leniency and the cost of deposits - Iselin, Michael; Nicoletti, Allison; Ott, Jacob; Zhang, Haiwen Helen (Review of Accounting Studies, 2025)
Abstract We examine whether variation in regulatory leniency is associated with the cost of deposits in the banking industry. We predict that lenient regulatory supervision allows for greater bank risk-taking due to delayed intervention, resulting in a higher cost of deposits. Our main finding is a positive association between banks’ cost of uninsured deposits and the leniency of their state regulators, incremental to observable measures of risk and performance. We further show that this result is stronger for riskier banks and when uninsured depositors have a greater ability or incentive to influence deposit rates. These findings suggest that the leniency of bank regulators is priced in uninsured deposit rates and further our understanding of the factors associated with regulatory leniency in the banking industry.